Ubiquitination of HLA-DO by MARCH family E3 ligases - Jahnke, Martin (Blackwell Publishing Ltd, 2013)
HLA-DO (DO) is a nonclassical MHC class II (MHCII) molecule that negatively regulates the ability of HLA-DM to catalyse the removal of invariant chain-derived CLIP peptides from classical MHCII molecules. Here, we show that DO is posttranslationally modified by ubiquitination. The location of the modified lysine residue is shared with all classical MHCII beta chains, suggesting a conserved function. Three membrane-associated RING-CH (MARCH1, 8 and 9) family E3 ligases that polyubiquitinate MHCII induce similar profiles of polyubiquitination on DOβ. All three MARCH proteins also influenced trafficking of DO indirectly by a mechanism that required the DOβ encoded di-leucine and tyrosine-based endocytosis motifs. This may be the result of MARCH-induced ubiquitination of components of the endocytic machinery. MARCH9 was by far the most efficient at inducing intracellular redistribution of DO but did not target molecules for lysosomal degradation. The specificity of MARCH9 for HLA-DQ and HLA-DO suggests a need for common regulation of these two MHC-encoded molecules.